2021
DOI: 10.1038/s41420-021-00551-8
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA LINC00284 facilitates cell proliferation in papillary thyroid cancer via impairing miR-3127-5p targeted E2F7 suppression

Abstract: Accumulating evidence has suggested that long noncoding RNAs (lncRNAs) exert crucial modulation roles in the biological behaviors of multiple malignancies. Nonetheless, the specific function of lncRNA LINC00284 in papillary thyroid cancer (PTC) remains not fully understood. The objective of this research was to explore the influence of LINC00284 in PTC and elucidate its potential mechanism. The Cancer Genome Atlas (TCGA), gene expression omnibus (GEO) datasets were used to analyze LINC00284 expression differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…FOXD2-AS1 was recognized as a molecular biomarker and participated in chemo-resistance, malignant proliferation, invasion, and immunosuppression (46,(51)(52)(53)(54)(55). Recently, a study demonstrated that overexpression of FOXD2-AS1 was associated with poor clinical outcomes in PTC (57)(58)(59). GI-associated ceRNA regulatory network should be evaluated in the future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FOXD2-AS1 was recognized as a molecular biomarker and participated in chemo-resistance, malignant proliferation, invasion, and immunosuppression (46,(51)(52)(53)(54)(55). Recently, a study demonstrated that overexpression of FOXD2-AS1 was associated with poor clinical outcomes in PTC (57)(58)(59). GI-associated ceRNA regulatory network should be evaluated in the future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed that GILS could identify the BRAF mutation status and share commonalities with clinical prognostic parameters. In addition, lncRNA, mRNA & miRNA likely work together to form a competing endogenous RNA (ceRNA) regulatory network, which could be used as prognostic markers in cancers ( 57 – 59 ). GI-associated ceRNA regulatory network should be evaluated in the future studies.…”
Section: Discussionmentioning
confidence: 99%
“…By combination of correlation analysis, expression analysis and survival analysis, miR-3127-5p and miR-2114-3p were selected as the two most potential downstream binding miRNAs of LRRC75A-AS1 in breast cancer. Both of the two miRNAs have been reported to be involved in initiation and progression of human malignancies, including osteosarcoma (Wang et al, 2021), papillary thyroid cancer (Zhou et al, 2021), colorectal cancer (Ma et al, 2021) and ovarian cancer (Yu Z et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The long and short diameters of tumors in mice were recorded weekly with a vernier caliper. Volume = (long diameter × short diameter)2 × 0.5 [ 24 ]. Four weeks later, the mice were anesthetized with pentobarbital sodium (30 mg/kg) and the tumors were weighed.…”
Section: Methodsmentioning
confidence: 99%